Studi Analisis Konten Dalam Drama Korea Selatan ”The Auditors”: Representasi Etika Pofesi Auditor - Gani, Nadia Saputri; Niswatin, Niswatin; Yusuf, Nilawaty (Journal of Applied Accounting, 2025)
This study aims to analyze the representation of auditor professional ethics in the South Korean drama “The Auditors”, and to compare it with the reality of the auditing profession in Indonesia. This research employs a qualitative approach with content analysis on the drama’s visual narrative. The results show that ethical principles such as integrity, objectivity, professional competence, confidentiality, and professional behavior are accurately represented in the drama. However, ethical violations are still common in Indonesian practice due to organizational pressure and weak oversight. This drama also highlights the potential of popular media as an educational tool that shapes a positive perception of the auditing profession. Keywords: Auditor Ethics; Korean Drama; Independence; Code Of Ethics; Media Representation